2023
DOI: 10.3389/fimmu.2023.1200939
|View full text |Cite
|
Sign up to set email alerts
|

Splenic SUMO1 controls systemic inflammation in experimental sepsis

Abstract: IntroductionThe recent discovery of TAK981(Subasumstat), the first-in-class selective inhibitor of SUMOylation, enables new immune treatments. TAK981 is already in clinical trials to potentiate immunotherapy in metastatic tumors and hematologic malignancies. Cancer patients have more than ten times higher risk of infections, but the effects of TAK981 in sepsis are unknown and previous studies on SUMO in infections are conflicting.MethodsWe used TAK981 in two sepsis models; polymicrobial peritonitis (CLP) and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Its anatomical position within the systemic circulation allows it to act as a central point for the immune system, recruiting and activating immune cells like macrophages and T cells when inflammatory signals are detected ( 35 ). When the gastrointestinal barrier is breached, bacteria and toxins, notably lipopolysaccharides (LPS), enter the bloodstream and trigger spleen reactions ( 36 , 37 ). Recent studies revealed that mice undergoing splenectomy exhibited more pronounced mucositis when exposed to DSS compared to sham-DSS mice, as evidenced by factors like mortality rate, stool consistency, gut barrier defects, serum cytokine levels, and blood bacterial counts.…”
Section: Introductionmentioning
confidence: 99%
“…Its anatomical position within the systemic circulation allows it to act as a central point for the immune system, recruiting and activating immune cells like macrophages and T cells when inflammatory signals are detected ( 35 ). When the gastrointestinal barrier is breached, bacteria and toxins, notably lipopolysaccharides (LPS), enter the bloodstream and trigger spleen reactions ( 36 , 37 ). Recent studies revealed that mice undergoing splenectomy exhibited more pronounced mucositis when exposed to DSS compared to sham-DSS mice, as evidenced by factors like mortality rate, stool consistency, gut barrier defects, serum cytokine levels, and blood bacterial counts.…”
Section: Introductionmentioning
confidence: 99%